Delayed presentation of traumatic diaphragmatic hernia: a case report - Che Alhadi, Shahidah; Mohamad, Ikhwan Sani; Ghulam Rasool, Syed Ibrahim; Zakaria, Zaidi (International Organization Of Scientific Research (IOSR), 2013)
Traumatic diaphragmatic hernias are an unusual presentation of trauma. The diagnosis is often missed because of non-specific clinical signs, and the absence of additional intra-abdominal and thoracic injuries. Thus, a delay in diagnosis may occur which, in the presence of obstruction and/or strangulation, is associated with a high mortality and morbidity.